271 Beta-adrenergic agonists increase maximal output of oxidative phosphorylation in bovine satellite cells. (30th November 2020) - Sieck, Renae L; Treffer, Leah K; Viana, Martonio Ponte; Khalimonchuk, Oleh; Schmidt, Ty B; Yates, Dustin T; Petersen, Jessica L
Abstract: Beta-adrenergic agonists (βAA) are widely used supplements in beef production to improve feed efficiency and increase lean muscle mass, yet little is known about the molecular mechanism by which βAA achieve this outcome. Our objective was to identify the influence of Ractopamine HCl (RH) and Zilpaterol HCl (ZH) on mitochondrial function in muscle stem cells. Satellite cells were isolated from skeletal muscle of cattle (n = 4) and yak (n = 1) at harvest. Cells were exposed to ZH, RH, or no βAA in replicates of four. Real-time measurements of oxygen consumption rates (OCR) and extracellular acidification rates (ECAR) were recorded using intracellular flux analysis. Incubation of bovine (n = 4) cells with either ZH or RH increased maximal respiration (P = 0.004) and spare respiratory capacity (P = 0.013). When yak cells were included, the response to treatment was similar (P = 0.006 and P = 0.006), but an animal effect was also observed (P < 0.02), presumably due to differences in genetic background. These findings indicate that βAA-treated cells have the capacity to respond more efficiently to increased energy demands than non-supplemented cells. Beta-adrenergic agonists improve the efficiency of muscle stem cells in part by modifying mitochondrial function.